Comparative genomics revealed adaptive admixture in Cryptosporidium hominis in Africa. Issue 1 (23rd January 2021) - Tichkule, Swapnil; Jex, Aaron R.; van Oosterhout, Cock; Sannella, Anna Rosa; Krumkamp, Ralf; Aldrich, Cassandra; Maiga-Ascofare, Oumou; Dekker, Denise; Lamshöft, Maike; Mbwana, Joyce; Rakotozandrindrainy, Njari; Borrmann, Steffen; et al.
Abstract : Cryptosporidiosis is a major cause of diarrhoeal illness among African children, and is associated with childhood mortality, malnutrition, cognitive development and growth retardation. Cryptosporidium hominis is the dominant pathogen in Africa, and genotyping at the glycoprotein 60 ( gp60 ) gene has revealed a complex distribution of different subtypes across this continent. However, a comprehensive exploration of the metapopulation structure and evolution based on whole-genome data has yet to be performed. Here, we sequenced and analysed the genomes of 26 C . hominis isolates, representing different gp60 subtypes, collected at rural sites in Gabon, Ghana, Madagascar and Tanzania. Phylogenetic and cluster analyses based on single-nucleotide polymorphisms showed that isolates predominantly clustered by their country of origin, irrespective of their gp60 subtype. We found a significant isolation-by-distance signature that shows the importance of local transmission, but we also detected evidence of hybridization between isolates of different geographical regions. We identified 37 outlier genes with exceptionally high nucleotide diversity, and this group is significantly enriched for genes encoding extracellular proteins and signal peptides. Furthermore, these genes are found more often than expected in recombinant regions, and they show a distinct signature of positive or balancing selection. We conclude that: (1) the metapopulation structure of C. hominis can only be accurately captured by whole-genome analyses; (2) local anthroponotic transmission underpins the spread of this pathogen in Africa; (3) hybridization occurs between distinct geographical lineages; and (4) genetic introgression provides novel substrate for positive or balancing selection in genes involved in host–parasite coevolution.